PD-L1 deficiency exacerbates colitis severity by remodeling gut microbiota in inflammatory bowel disease - Ma, Yixian; Suo, Jinshan; Sheng, Siqi; Chen, Ling (Frontiers in Immunology, 2025)
BackgroundInflammatory bowel disease (IBD) is a chronic autoimmune disorder driven by gut microbiota dysbiosis. As an essential immune checkpoint, Programmed death-ligand 1 (PD-L1) has been implicated in modulating gut microbiota composition. However, the precise role of PD-L1 in shaping metagenomic profiles during IBD-associated colitis remains unexplored.MethodsDSS-induced colitis was established in both PD-L1 knockout (Pdcd1lg1-/-) mice and wild-type (wt) control mice. Clinical parameters, including disease activity index (DAI), body weight changes, colon length, and histopathological alterations, were systematically evaluated using non-parametric Kruskal-Wallis tests and ANOVA to compare colitis severity between genotypes.ResultsPD-L1 knockout mice exhibited exacerbated colitis, manifesting significantly greater weight loss (p<0.05 vs. wt_DSS), colonic shortening (p<0.05), and DAI scores (p<0.05) and inflammatory changes. PD-L1 knockout mice showed distinct dysbiosis, with enriched pathobionts (Escherichia coli, p=0.006; Bacteroides thetaiotaomicron, p=0.015) and depletion of commensals (Tritrichomonas foetus, p<0.001; Ligilactobacillus murinus). Alpha diversity analysis using Chao1 index revealed statistically significant differences between experimental groups (p=0.05). The transporters downregulate anti-inflammatory SCFA metabolism. KEGG enrichment analysis of differentially expressed genes (DEGs) revealed significant associations with immune and inflammatory pathways in PD-L1 knockout mice.ConclusionPD-L1 deficiency aggravates colitis by driving pathogenic microbiota alterations and impairing microbial metabolic homeostasis, highlighting its dual regulatory roles in immune homeostasis and microbiome dynamics.